Revision of the ARRIVE guidelines: rationale and scope. Issue 1 (12th June 2018) - Percie du Sert, Nathalie; Hurst, Viki; Ahluwalia, Amrita; Alam, Sabina; Altman, Douglas G; Avey, Marc T; Baker, Monya; Browne, William; Clark, Alejandra; Cuthill, Innes C; Dirnagl, Ulrich; Emerson, Michael; et al.
Abstract : In 2010, the NC3Rs published the Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines to improve the reporting of animal research. Despite considerable levels of support from the scientific community, the impact on the quality of reporting in animal research publications has been limited. This position paper highlights the strategy of an expert working group established to revise the guidelines and facilitate their uptake. The group's initial work will focus on three main areas: prioritisation of the ARRIVE items into a tiered system, development of an explanation and elaboration document, and revision of specific items.